Integrin VLA-5 and FAK are Good Targets to Improve Treatment Response in the Philadelphia Chromosome Positive Acute Lymphoblastic Leukemia - Hu, Zhongbo; Slayton, William B. (Frontiers in Oncology, 2014)
Acute lymphoblastic leukemia bearing the Philadelphia chromosome is among the most difficult types of ALL to cure. However, the advent of targeted tyrosine kinase inhibitor (TKI) imatinib has ushered in a new era of treatments that have the potential to be less toxic to patients. Integrins and tyrosine kinases play important roles in mediating and transducing signals for cell survival and suppressing apoptosis. Focal adhesion kinase (FAK) is a non-receptor type tyrosine kinase that is constitutively activated in Ph+ ALL. We sought to investigate the specificity of integrin α5β1 (VLA-5) on Ph+ leukemia by its expression and function. We found VLA-5 expression increases after serum starvation. Integrin α5 inhibitory antibody inhibited adhesion of Ph+ leukemia to human fibronectin and acted synergistically with imatinib to induce Ph+ leukemia cell apoptosis. We used different strategies to block integrin signaling and knocked down the expression of integrin VLA-5 to observe the effect on proliferation and engraftment of Ph+ leukemia cells in immunodeficient mice. We found that blocking integrin activity by incubating Ph+ leukemia cells with disintegrin, a peptide inhibitor of integrins, or α5 inhibitory antibody, or knocking down the α5 integrin subunit impaired and delayed the engraftment of Ph+ leukemia in immunodeficient mice. We then treated mice xenografted with Ph+ leukemia cells with the FAK inhibitor TAE226 in combination with a BCR–ABL TKI nilotinib. While 2 weeks of treatment with TAE226 alone did not significantly inhibit leukemia growth in mice, TAE226 in combination with nilotinib provided the most optimum growth inhibition at 4–6 weeks. We conclude that blocking VLA-5 signaling or combining FAK inhibitors with TKI targeting BCL/ABL might be good strategies to improve treatments in patients with Ph+ ALL. By altering Ph+ leukemia cell interactions with the microenvironment, we may increase their susceptibility to therapy targeting BCR/ABL.